Prevalence of Tinnitus and Its Associated Factors in the PERSIAN Guilan Cohort Study - Rasool Panahi; Mir Mohammad Jalali; Farahnaz Joukar; Saman Maroufizadeh; Mohammadreza Naghipour; Fariborz Mansour-Ghanaei (Iranian Journal of Otorhinolaryngology, 2023)
Introduction:Tinnitus can be associated with many auditory and non-auditory factors, and its prevalence varies widely in the literature. There is no large sample of published data on tinnitus prevalence and its associated factors in Iran. Here, we analyzed the PERSIAN Guilan Cohort Study (PGCS) data and reported the prevalence of tinnitus and some of the risk factors related to tinnitus in the Iranian population. Materials and Methods:This cross-sectional study was conducted on 10520 men and women between 35 and 70 years old. The prevalence of tinnitus and associations between tinnitus and age, sex, habitat, marital status, employment status, socioeconomic status, educational level, lifestyle habits, and comorbid diseases were examined using simple and multiple logistic regression analyses.Results:The prevalence of tinnitus was 6.4% in this study. Based on the adjusted analysis, only older age (odds ratio: 2.60, 95% confidence interval: 1.88 – 3.60), residency in a rural area (odds ratio: 1.22, 95% confidence interval: 1.03 – 1.44), cigarette smoking (odds ratio:1.33, 95% confidence interval: 1.04 – 1.72), and having other comorbidities (odds ratio: 2.75, 95% confidence interval: 2.19 – 3.44) were related to tinnitus. In addition, the results of subgroup analyses by sex were mostly consistent with the overall analysis.Conclusions:Our results revealed that the prevalence of tinnitus in the north of Iran is comparable with other communities. Age and other comorbidities were among the most related factors to tinnitus.